Prise en compte de la biodiversité dans les projets d’aménagement : comment améliorer la commande des études environnementales ? - Sylvie Vanpeene-Bruhier; Pierre-André Pissard; Martin Kopf (Développement Durable et Territoires)
Better biodiversity integration (in particular daily life nature and ecosystems functioning) strengthen impact studies requirement, compensatory measures and ecological network (Trame verte et bleue) integration into both fitting out projects and town planning documents. This requires numerous and relevant environmental datas in order to evaluate project possible impacts. Based on cities biodiversity studies and transportation facilities impact, we point out gaps or problems in inventory needs or natural datas recollection formulation. We provide ideas for better relations and better mutual expectations between planners and natural data providers.